Educational research and development : trends, issues and challenges - Kogan, Maurice (OECD ParisFR, 1995)
Provides an up-to-date view of the issues and prospects for educational research and development and points to the issues that will occupy the attention of researchers, policy-makers and practioners through the remainder of the decade and well into the next century.